2020
DOI: 10.1111/sum.12644
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal variations on soil CO2 fluxes in tropical silvopastoral systems

Abstract: Soil respiration is a very important component of the global carbon cycle, considered as the second most important carbon (C) flux to the atmosphere and is directly affected by global warming (Xu & Qi, 2001; Bond-Lamberty et al., 2004; Arredondo et al., 2018). It is defined as the sum of autotrophic respiration (i.e. roots and fungi) and heterotrophic respiration (i.e. soil microorganisms that break down organic matter and soil fauna) and is influenced by environmental factors, such as soil and ambient tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Higher C and nutrient input from litterfall in STP favour soil nutrient recycling, which explains the increase in SOC content. The variations in carbon emissions from soil respiration between STP and GM also affect the accumulation of SOC in these livestock systems (Adame‐Castro et al, 2020; Villanueva‐López et al, 2016). These findings showed that the presence of scattered trees in livestock grazing systems (STP) enhances C storage at different soil depths as well as in woody biomass and merits consideration in strategies to mitigate the carbon emissions from animal production systems and for the successful achievement of the SDGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher C and nutrient input from litterfall in STP favour soil nutrient recycling, which explains the increase in SOC content. The variations in carbon emissions from soil respiration between STP and GM also affect the accumulation of SOC in these livestock systems (Adame‐Castro et al, 2020; Villanueva‐López et al, 2016). These findings showed that the presence of scattered trees in livestock grazing systems (STP) enhances C storage at different soil depths as well as in woody biomass and merits consideration in strategies to mitigate the carbon emissions from animal production systems and for the successful achievement of the SDGs.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing atmospheric concentrations of greenhouse gases (GHG) are recognized as the main cause of climate change (Adame‐Castro et al, 2020; Villanueva‐López et al, 2019). GHG emissions have increased by more than 40% since preindustrial times, with CO 2 concentrations in the atmosphere increasing from 278 ppm in 1750 to 414 ppm in 2020 (Krishnapriya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (2020) found that cattle grazing grass-dominated cover crops reduced CO 2 efflux compared with grazing legume-dominated cover crops, and overall, grazing compared with nongrazing did not affect cumulative CO 2 emissions. Research on soil respiration differences between forages in silvopastures is limited; however, Adame-Castro et al (2020) reported no cumulative flux differences between Panicum maximum Jacq. and Cynodon plectostachyus (K.…”
Section: Introductionmentioning
confidence: 99%
“…Research on soil respiration differences between forages in silvopastures is limited; however, Adame‐Castro et al. (2020) reported no cumulative flux differences between Panicum maximum Jacq. and Cynodon plectostachyus (K.…”
Section: Introductionmentioning
confidence: 99%